The Making and Unmaking of Whiteness - Allan, Bérubé; Birgit Brander, Rasmussen; Brander Rasmussen, Birgit; Dalton, Conley; Eric, Klinenberg; Eric, Lott; Howard, Winant; Irene J., Nexica; Jasbir Kaur, Puar; John, Hartigan Jr; Klinenberg, Eric; Mab, Segrest; et al. (Duke University Press, 2001)
Bringing together new articles and essays from the controversial Berkeley conference of the same name, The Making and Unmaking of Whiteness presents a fascinating range of inquiry into the nature of whiteness. Representing academics, independent scholars, community organizers, and antiracist activists, the contributors are all leaders in the "second wave" of whiteness studies who collectively aim to combat the historical legacies of white supremacy and to inform those who seek to understand the changing nature of white identity, both in the United States and abroad.With essays devoted to theories of racial domination, comparative global racisms, and transnational white identity, the geographical reach of the volume is significant and broad. Dalton Conley writes on "How I Learned to Be White." Allan Bérubé discusses the intersection of gay identity and whiteness, and Mab Segrest describes the spiritual price white people pay for living in a system of white supremacy. Other pieces examine the utility of whiteness as a critical term for social analysis and contextualize different attempts at antiracist activism. In a razor-sharp introduction, the editors not only raise provocative questions about the intellectual, social, and political goals of those interested in the study of whiteness but assess several of the topic's major recurrent themes: the visibility of whiteness (or the lack thereof); the "emptiness" of whiteness as a category of identification; and conceptions of whiteness as a structural privilege, a harbinger of violence, or an institutionalization of European imperialism.Contributors. William Aal, Allan Bérubé, Birgit Brander Rasmussen, Dalton Conley, Troy Duster, Ruth Frankenberg, John Hartigan Jr., Eric Klinenberg, Eric Lott, Irene J. Nexica, Michael Omi, Jasbir Kaur Puar, Mab Segrest, Vron Ware, Howard Winant, Matt Wray